2011
DOI: 10.1148/radiol.11110162
|View full text |Cite
|
Sign up to set email alerts
|

The Secretory Flow of Pancreatic Juice in the Main Pancreatic Duct: Visualization by Means of MRCP with Spatially Selective Inversion-Recovery Pulse

Abstract: The physiologic flow of the pancreatic juice can be visualized noninvasively with serial MRCP by using a spatially selective IR pulse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The Time-SLIP technique can be used to evaluate blood flow dynamics and pancreatic secretions. [2][3][4][5][6][7][8][9][10] Moreover, Time-SLIP has been used to evaluate CSF motion in the brain. 1,[11][12][13][14] Using Time-SLIP, we detected several CSF flow patterns that could not be resolved by traditional imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The Time-SLIP technique can be used to evaluate blood flow dynamics and pancreatic secretions. [2][3][4][5][6][7][8][9][10] Moreover, Time-SLIP has been used to evaluate CSF motion in the brain. 1,[11][12][13][14] Using Time-SLIP, we detected several CSF flow patterns that could not be resolved by traditional imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Time‐SLIP is a technique based on arterial spin‐labeling methods; without the need for contrast material, it demonstrates the flow of blood, cerebrospinal fluid (CSF), pancreatic juice, and flow in the salivary gland duct . Although the Time‐SLIP technique can measure the travel distance of flow in 2D planes, we found no reports that quantified the volume flow rate (VFR, mm 3 /sec).…”
mentioning
confidence: 95%
“…Some studies have evaluated the excretion flow dynamics of pancreatic juice and bile using cine‐dynamic magnetic resonance cholangiopancreatography (MRCP) with a spatially selective inversion recovery (IR) pulse 4,5 . These studies demonstrated that the secretion of bile and pancreatic juice was irregular and that reverse bile flow in the extrahepatic bile duct was a physiological phenomenon.…”
mentioning
confidence: 99%